Ivan : the remarkable true story of the shopping mall gorilla - Applegate, Katherine (Clarion Books, Houghton Mifflin Harcourt, 2014)
"The true story of Ivan, known as the Shopping Mall Gorilla, who lived alone in a small cage for almost 30 years before being relocated to the gorilla habitat at ZooAtlanta."--